Pemanfaatan Tumbuhan Dalam Proses Pewarnaan Kain Tenun Ikat Di Desa Harona Kalla Kecamatan Laboya Barat Kabupaten Sumba Barat - Vianros Ana Ate; Yanti Daud; Alan Ch Sabuna (Indigenous Biologi : Jurnal Pendidikan dan Sains Biologi, 2020)
This study aims to determine the types of natural dye plants, organs or plant parts used in the process of coloring woven cloth, and the processing of plants to produce colors as dyes of woven cloth, colors produced from plants dyed woven cloth dyes in Harona Kalla Village, West Laboya sub-district, West Sumba Regency. The method used is a qualitative method with semi-structural observation and interview techniques that refer to the list of questions that have been prepared. Based on the results of research in Harona Kalla Village, west Laboya sub-district, West Sumba Regency, three types of natural coloring plants were found, namely turi leaves (Sesbania grandiflora), turmeric rhizome (Curcuma domestica L), mahogany (Swietenia mahagoni L). In addition to coloring plants there are plants that are used as additives in coloring namely fence kedondong (Lannae nigritana), baiduri (Calotropis gigantea), betel lime and iron rust / vinegar. The organs in the coloring process are bark, rhizome and leaves. And the processing of plant organs is done pounding and boiling. The purpose of adding lime is to lock the color so that it does not fade easily. Based on the results of the study, the colors produced from plants in the village of Harona Kalla are turi leaves (Sesbania grandiflora) which are pounded and produce a green color. Turmeric (Curcuma domestica L) which is pounded and boiled produces yellow, mahogany bark (Swietenia mahagoni L) which is boiled produces a black color. The conclusion of this research is that it is necessary to design efforts to cultivate color-producing plants which are non-wood forest products to support the sustainable industry in Harona Kalla Village, for the cultivation of species of color-producing plants.